The Effect of Motivation, Work Discipline, and Work Environment on Employee Performance - Dwiyana Erawati; Mokhamad Natsir; Pudjo Sugito (Institut Agama Islam Sunan Giri Ponorogo, 2026)
The purpose of this study is to describe and analyze the influence of motivation, work discipline, and the work environment on employee performance at the Magetan Regency Transportation Agency. The sampling technique used in this study was a non-probability sampling technique with saturated (census) sampling, with a sample size of 89 respondents. The research method used was a quantitative approach with the assistance of SPSS version 20. Data analysis used multiple linear regression. The results of the study indicate that: 1) Motivation, work discipline, and the work environment simultaneously influence employee performance at the Magetan Regency Transportation Agency. 2) Partially, the motivation variable (X1) has a positive and significant influence on employee performance at the Magetan Regency Transportation Agency. 3) Partially, the work discipline variable (X2) has a positive and significant influence on employee performance at the Magetan Regency Transportation Agency. 4) Partially, the work environment variable (X3) has a positive and significant influence on employee performance at the Magetan Regency Transportation Agency. 5) Work discipline is the variable with the dominant influence on employee performance at the Magetan Regency Transportation Agency.